Clinical course of alopecia after COVID-19. (June 2021) - Suzuki, Tetsuya; Kutsuna, Satoshi; Saito, Sho; Kawashima, Akira; Okuhama, Ayako; Kanda, Kohei; Sato, Lubna; Inada, Makoto; Akiyama, Yutaro; Ide, Satoshi; Nakamura, Keiji; Nakamoto, Takato; et al.
Graphical abstract: